EMPLOYEE PRO-ENVIRONMENTAL BEHAVIOR: A BIBLIOMETRIC REVIEW FROM 2000-2024 - Rayner Dillon Wibisono; Septian Salim (Riviera Publishing, 2025)
This study offers a thorough bibliometric analysis of Employee Pro-environmental Behavior (EPB) research from 2000 to 2024. The study used data from the Web of Science (WoS) and tool: VOSviewer to examine 766 articles, aiming to discern prominent research themes and trends in EPB. Narrow down to 55 articles, thematic analysis between four principal clusters were identified: Influential Factors, Workplace Performance, Pro-environmental Adoption, and Employee Outcomes. The bibliometric study indicates an increasing focus on Green Human Resource Management (HRM) and Corporate Social Responsibility (CSR) as essential factors influencing Environmental Performance Behavior (EPB), particularly within the hotel and tourist industries. The review emphasizes historical patterns, prominent writers, prolific publications, and collaborative networks that have influenced the discipline. This study offers an overview of the changing academic scene and suggests avenues for future research, especially in underexamined domains like as digital technology adoption and the influence of spiritual leadership on EPB.